2013
DOI: 10.1167/13.14.17
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the interaction between low and intermediate levels of spatial vision at different periods of development

Abstract: Although much research has investigated the visual development of lower (local) and higher levels (global) of processing in isolation, less is known about the developmental interactions between mechanisms mediating early- and intermediate-level vision. The objective of this study was to evaluate the development of intermediate-level vision by assessing the ability to discriminate circular shapes (global) whose contour was defined by different local attributes: luminance and texture. School-aged children, adole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
1

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 47 publications
1
4
1
Order By: Relevance
“…Our method allows the dissociation of sensitivity to local contour deformations from the integration of that information and the results lead to the suggestion that sensitivity to the local features of the RF contour such as curvature information is, instead, improving as a function of age. This is contrary to the conclusions of Perreault et al (2013), whose data suggested global processing was not yet mature in primary school-age children but that sensitivity to local contour information was mature in this age group. The authors reached this conclusion on the basis that children were less sensitive to fully modulated RF3 and RF5 patterns (globally processed frequencies) than adults, but groups were equally sensitive to a fully modulated RF10 (a locally processed frequency).…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Our method allows the dissociation of sensitivity to local contour deformations from the integration of that information and the results lead to the suggestion that sensitivity to the local features of the RF contour such as curvature information is, instead, improving as a function of age. This is contrary to the conclusions of Perreault et al (2013), whose data suggested global processing was not yet mature in primary school-age children but that sensitivity to local contour information was mature in this age group. The authors reached this conclusion on the basis that children were less sensitive to fully modulated RF3 and RF5 patterns (globally processed frequencies) than adults, but groups were equally sensitive to a fully modulated RF10 (a locally processed frequency).…”
Section: Discussioncontrasting
confidence: 99%
“…The data indicate that all participants showed improvements in threshold as more cycles of deformation were added and the improvements were larger than those predicted by probability summation (using either method for this calculation), indicating global contour integration is occurring and that it occurs at all ages. The data suggest sensitivity to deformation in globally processed RF patterns improves from primary school age to early adulthood for samples whose cognitive ability is in the normal range, consistent with data reported by Wang et al (2009) and Perreault et al (2013). However, these changes in sensitivity to RF patterns across development cannot be accounted for by increased effectiveness of global contour integration, as our data suggests there is no improvement in the steepness of integration slopes across this period of development.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations